Disseminated Cryptococcal Infection in Apparently Immunocompetent Child: a Case Report - Basnet, Srijana; Shrivastav, Shreya; Kumar Gupta, Dipak (Journal of BP Koirala Institute of Health Sciences, 2023)
Cryptococcal infection is the third most common fungal infection which commonly affects immune-compromised hosts but is increasingly recognized in immunocompetent hosts also. Here, we report disseminated cryptococcosis in an apparently immunocompetent child presenting with high-grade fever, headache and altered sensorium for one month. He had pallor, lymphadenopathy, skin lesions, decreased vision, sixth and seventh cranial nerve palsy, and hepatosplenomegaly. Cerebrospinal fluid analysis report, contrast-enhanced Computed Tomography of brain, and bone-marrow aspiration were normal. The diagnosis was confirmed on bone marrow biopsy. Early diagnosis and timely management of this disease would be life-saving for many children.